(3efGbH GdTjN Ydj Hf eMeO (B((3aJMG(B) (3GdYcGQjs - (3CHh GdMSf Ydj Hf eMeO Hf Ydj GdYcGQj, GdYcGQj,J (B1118 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdUdGI hGdSdGe Ydi SjOfG eMeO s
(3BNQgG (B:s
(3jCJjc ef ehdGc eGJQLi fUQ ef Gddg haJM bQjH gfG GfJgi eG hLOJg ebjOkG aj efGbH GdTjN Gdhdi GdUGdM SjOi Ydi GdYcGQi s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B14s
(3Odjd eDQN GdeZQH (B- (3U (B259 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B427 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs